ANALISIS PERUBAHAN IKLIM LOKAL DAN DEBIT SUNGAI DI DAS CIDANAUANALYSIS OF LOCAL CLIMATE CHANGE AND DISCHARGE IN CIDANAU WATERSHED - Fadli Irsyad; Satyanto Krido Saptomo; Budi Indra Setiawan (Agromet, 2011)
Climate change causes uncertainty in water availability. The change may include annual rainfall, evapotranspiration and the shift of rainy and dry seasons, thus, it affects hydrological response in the region. Water demand will increase over time with population, industrial and business growth but the water availability has not been ascertained to sustainably satisfy those needs.  Cidanau Watershed has wetland ecosystem so-called the Rawa Danau (Caldera), with an area of around 2,500 ha. This watershed receives average annual rainfall around 2,500 mm. Climate change especially the local climate in the region of Cidanau was analyzed to illustrate how the relationship with Cidanau river discharge. It is expected that climate change does not affect the water availability in the watershed. In this study, the analysis of local climate change and its impact on the availability of water resources on Cidanau Watershed was based on climate trends, water balance analysis, and estimation of  discharge of Cidanau Watershed. This research was carried out using climate data and discharge from 1996 until 2010. The results showed that climate variables have changed from 1996 to 2010. This change mainly occurred in temperature, annual rainfall, and evapotranspiration. Based on the analysis, the discharge of Cidanau Watershed will decrease due to changes in rainfall and evapotranspiration. The estimated minimum river discharge of Cidanau Watershed ranges from 0.5 to 1 m3/s until 2050.